Framework development for engineering technology - Haron, Habibah @ Norehan; Hussain, Noor Hamizah; Ali, Rosmah; Abdullah, Morina; Radin Salim, Kamilah; Mohamed, Zainai; Mohd Ismail, Kamsiah (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper reports a study on the framework development for application-based teaching and learning in engineering technology education in Malaysia. The research interest was mooted from a report ―The Future of Engineering Education in Malaysia, issued by the Ministry of Higher Education (MOHE) in 2007. The nation needs to produce two types of engineers –theoretical and research-based engineers, application and practice-oriented engineers. The latter group is an industrial-ready graduate who is immediately able to serve as a shop floor engineer or take up a new job as an entrepreneur. This group of graduates will function as engineering technology professionals, thus, serves the engineering technology profession. A Mixed-method consisting of sequential exploratory and explanatory was designed for data collection. The extent of how much planned actions actually materialized and what further actions should be taken were investigated. Relevant findings from this research show that Malaysian Technical Universities are on the right track in producing premier Technical Vocational Education and Training (TVET) graduates; as evidenced from the establishment of specific faculty to support this sector of education. However, there are still critical areas that need attention, and one of them discussed in this paper is the manpower responsible for delivering the engineering technology curriculum. A framework for manpower requirement to guide the ongoing efforts to improve Engineering Technology education is presented.